1999
DOI: 10.1109/77.784942
|View full text |Cite
|
Sign up to set email alerts
|

Flux pinning due to MgO particle additions in partial-melt processed Bi-2212 bulk

Abstract: In order t o introduce effective pinning centers into Bi-2212 superconducting bulk, the addition of small MgO particles t o Bi-2212 bulk and its effect on flux pinning were studied. Bi-2212 bulk samples were prepared by employing a normal partial-melting process, with a 0-8 vol.% of MgO particles addition. T h e morphology of Bi-2212 with MgO doping was investigated by means of XRD and EPMA. T h e magnetization and critical current densities (Jc's) in various magnetic fields and temperatures were measured by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…The introduction of 200 nm MgO particles into Bi-2212 bulk increases the critical current density in Bi-2212 in the low temperature region (below 30 K), implying that MgO particles act as effective pinning centres and enhance the flux pinning characteristics in Bi-2212 bulk [5]. However, similar addition of ultra-fine MgO particles (10 nm) did not enlarge the critical current density, contrary to expectations based on the flux pinning theory.…”
Section: Introductioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The introduction of 200 nm MgO particles into Bi-2212 bulk increases the critical current density in Bi-2212 in the low temperature region (below 30 K), implying that MgO particles act as effective pinning centres and enhance the flux pinning characteristics in Bi-2212 bulk [5]. However, similar addition of ultra-fine MgO particles (10 nm) did not enlarge the critical current density, contrary to expectations based on the flux pinning theory.…”
Section: Introductioncontrasting
confidence: 72%
“…Greater enhancement of magnetization hysteresis and the irreversibility field was observed in samples with MgO content of up to 20 mol.% (1.15 wt.%). This concentration of MgO is about 4-5 times lower than the MgO doping, used in [5]. Therefore, it is likely that the efficacy of flux pinning centers on J c depends not only on the size of MgO particles and their morphology, but also on the particle concentration in the Bi-2212 matrix.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It turned out that doping of Bi 2212 ceramics with MgO particles ~200 nm across increases the critical current density of the superconductor at low tempera tures (<30 K), which means improving the pinning center efficiency [9]. However, doping of Bi 2212 ceramics by ~10 nm nanoparticles did not raise the critical current densities, which contradicts the pin ning theory.…”
Section: Introductionmentioning
confidence: 95%
“…The incorporation of metal or oxide particles chemically inactive to high temperature supercon ductors (HTSs), such as magnesium oxide particles [3,4,[9][10][11][12][13][14], seems to be promising for raising the crit ical current in HTS structures, since they can serve as pinning centers. It has been also found that the incor poration of MgO in small amounts facilitates texturing of ceramics [4] and decreases the number of secondary phases [3].…”
Section: Introductionmentioning
confidence: 99%